Mediated Happiness and Digital Well-Being - Majkut, Paul (Nuevo Itinerario, 2015)
The king sat on one end of the scale and the other end was filled with gold until a balance was reached. The king’s worth was measured by his weight in gold. Presumably, this made him happy. He said that the gold on the opposite end of the scale made him happy, but we only have his word and monarchs are famously devious. In any case, whether the king said he was happy and even truly believed that he was happy when he said he was happy is beside the point. The point is: Was he really happy?